Multi-Algorithm Swath Consistency Detection for Multibeam Echosounder Data - Calder, Brian (The International Hydrographic Review, 2007)
It is unrealistic to expect that any single algorithm for pre-filtering Multibeam Echosounder data will be able to detect all of the “noise" in such data all of the time. This paper therefore presents a scheme for fusing the results of many pre-filtering sub-algorithms in order to form one, significantly more robust, meta-algorithm. This principle is illustrated on the problem of consistency detection in regions of sloping bathymetry. We show that the meta-algorithm is more robust, adapts dynamically to sub-algorithm performance, and is consistent with operator assessment of the data. The meta-algorithm is called the Multi-Algorithm Swath Consistency Detector.